2019
DOI: 10.1371/journal.pone.0214612
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with low handgrip strength in the older Korean population

Abstract: Hand grip strength (HGS) is a means to assess health status and physical abilities indirectly. Various factors are known to be related to HGS, but data on the factors influencing HGS in the Korean population are lacking. Recently, the Korea National Health and Nutrition Examination Survey (KNHANES) conducted by the Korea Centers for Disease Control and Prevention surveyed social status, nutrition, physical status, and other medical history including HGS. This study aimed to investigate the social, physical, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
48
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 41 publications
(61 reference statements)
9
48
0
1
Order By: Relevance
“…Although excessive drinking has been shown to be associated with sarcopenia [24], light-to-moderate alcohol intake has also been shown to have a protective effect against muscle mass loss [25]. Similar ndings as those observed in this study were observed in a European and Koran study [26]. Further research is needed to ascertain the positive effects of alcohol consumption on HGS, in view of many other factors that can manipulate the result, such as the amount of alcohol, which was not measured in the study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although excessive drinking has been shown to be associated with sarcopenia [24], light-to-moderate alcohol intake has also been shown to have a protective effect against muscle mass loss [25]. Similar ndings as those observed in this study were observed in a European and Koran study [26]. Further research is needed to ascertain the positive effects of alcohol consumption on HGS, in view of many other factors that can manipulate the result, such as the amount of alcohol, which was not measured in the study.…”
Section: Discussionsupporting
confidence: 90%
“…Perhaps this can be linked to other factors, such as occupation and physical activity of the smokers since most smokers comprised those with low socioeconomic status [27]. Although some studies have shown that smoking has negative effects on HGS [28,29], several other studies have shown mixed results on the effect of smoking [26,30]. Additionally, a study noted low HGS among smokers with COPD as a predictor of future acute respiratory events [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is a particularly good and quick tool to assess muscle strength. 27) In this study, the prevalence of osteoporosis was significantly associated with left-hand RHGS in women aged 60-69 years after adjusting for sociodemographic characteristics, lifestyle behaviors, and other health-related variables in the KNHANES data from 2014 to 2018. Furthermore, the osteoporosis risks were decreased by approximately 36.3% and 50.4% in levels 2 and 4, respectively.…”
Section: Discussionmentioning
confidence: 62%
“…The covariates included in this study were identified by referring to previously reported factors associated with decreased HGS. 27 )…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation